Chitosan chemistry review for living organisms encapsulation. (1st November 2022) - Meyer-Déru, Lorelei; David, Ghislain; Auvergne, Remi
Abstract: Microencapsulation is an emerging process in which an active substance is entrapped in a homogeneous or heterogeneous matrix to form capsules. This technique allows reducing the adverse effects of the external environment on encapsulated compounds, ensuring their stability through manipulation and transport besides enabling their controlled release. Microencapsulation is particularly suitable to protect sensitive materials such as living organisms, thus providing them an appropriate environment to behave and act as if they were in their natural habitat. The used matrix is generally composed of polymers, due to their ability to form flexible networks. Chitosan, a linear polysaccharide obtained from chitin, is a prime microencapsulation polymer by itself or in combination with other polymers owing to its cationic nature, biodegradability, non-toxicity and mucoadhesive properties. This review aims to present the diverse chitosan modifications, adaptations and crosslinking through the microencapsulation of somatic cells, bacteria, yeasts and microalgaes. Graphical abstract: Unlabelled Image